Peran Guru dalam Membangun Etika Peserta Didik - Sumo, Maimun; Koryataini, Lia (Al-Abshar: Journal of Islamic Education Management, 2023)
The teacher is someone who has an important role in student development starting from developing students' talents, giving advice, being a good role model, especially in building good ethics.In this case the school is a place to build student ethics, starting from ethics in speaking to teachers, parents, peers and others, ethics in dress, ethics in association, traffic ethics, ethics in business and other ethical ethics. The existence of this research aims to describe how the teacher's role in building student ethics. This study used the literature review method where fifteen articles and five books were analyzed which were the most significant to the research topic.In accordance with the research that has been done, the results show that the role of being a teacher in the process of building student ethics is very much needed because as an educator the teacher holds a very important role in the learning process. Ethics has many meanings, but based on a broader understanding, ethics is a guide to life, to live in a way that is in accordance with the rules and to act according to the rules.From this understanding it provides methods, directions for humans to live well and do positive things. Based on this research, it can be concluded that the teacher has an important role for students to guide, teach, give direction, especially in forming good ethics so that students with better ethics are formed than before. The role of a teacher is very important for students so that students can gain as much knowledge from the teacher